2004
DOI: 10.1093/nar/gkh858
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae TRT2 tRNAThr gene upstream of STE6 is a barrier to repression in MAT  cells and exerts a potential tRNA position effect in MATa cells

Abstract: A growing body of evidence suggests that genes transcribed by RNA polymerase III exhibit multiple functions within a chromosome. While the predominant function of these genes is the synthesis of RNA molecules, certain RNA polymerase III genes also function as genomic landmarks. Transfer RNA genes are known to exhibit extra-transcriptional activities such as directing Ty element integration, pausing of replication forks, overriding nucleosome positioning sequences, repressing neighboring genes (tRNA position ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…Three (ACO1, ARO8 and YEL033W) of the six genes showed a consistent but modest modification in transcript level by Northern blot analysis (Conesa et al, 2005). A similar tRNA position effect was also reported initially for the tRNA-Thr(CGU) gene upstream of CBT1 in the native chromosomal locus (Simms et al, 2004). However, more detail subsequent analysis demonstrated that tRNA-Thr(CGU) gene in its natural context serves as an insulator between STE6, an upstream gene, and CBT1, preventing the STE6 regulatory elements from affecting CBT1 transcription (Simms et al, 2008).…”
Section: Accepted M Manuscriptsupporting
confidence: 77%
“…Three (ACO1, ARO8 and YEL033W) of the six genes showed a consistent but modest modification in transcript level by Northern blot analysis (Conesa et al, 2005). A similar tRNA position effect was also reported initially for the tRNA-Thr(CGU) gene upstream of CBT1 in the native chromosomal locus (Simms et al, 2004). However, more detail subsequent analysis demonstrated that tRNA-Thr(CGU) gene in its natural context serves as an insulator between STE6, an upstream gene, and CBT1, preventing the STE6 regulatory elements from affecting CBT1 transcription (Simms et al, 2008).…”
Section: Accepted M Manuscriptsupporting
confidence: 77%
“…on adjacent transcription units (Simms et al 2004). In particular, the tRNA gene located adjacent to HMR acts as a barrier to protect nearby genes from the spread of heterochromatin (Donze et al 1999;Donze and Kamakaka 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, SUP4-o may be specifically acting as an initiator or terminator of gene-conversion tracts. In yeast, tRNA genes can cause replication fork pausing (Deshpande and Newlon 1996;Dubarry et al 2011), and can act as chromatin silencing barriers or insulators (Simms et al 2004;Simms et al 2008). tRNA gene sites are weakly recombinogenic when RNAP III collides with DNA polymerase (de la Loza et al 2009); and when essential replication genes are downregulated, Ty retrotransposons and tRNA genes are frequently found together at the breakpoints of chromosome rearrangements -indicates no replication stress, + indicates a low level of replication stress, and +++ indicates high levels of replication stress.…”
mentioning
confidence: 99%